Understanding Factors Related to Prolonged Trial of Detained Defendants in the Philippines - Narag, Raymund E. (International journal of offender therapy and comparative criminology, 2018)
Utilizing a combination of jail official data and qualitative data gathered through Focus Group Discussions and interviews with inmates, court actors, and jail officers, this article investigates the factors related to prolonged trial of detained defendants in the Philippines. Sensitizing concepts derived from Western literature are utilized to understand individual, court, and jail-level variations to prolonged detention. Results from official jail data show the magnitude and extent of the problem. The narrative data suggests the salience of organizational and cultural dynamics that lead to the delay of cases for detained defendants. Specifically, courts that are loosely coupled and subscribe to workgroup culture that condones leniency are more likely to be delayed. Implications to theory and policy are discussed.